Interprofessional Learning during an International Fieldwork Placement - Strong, J.; Chipchase, L.; Allen, S.; Eley, D.S.; McAllister, L.; Davidson, B. (International Journal of Practice-based Learning in Health and Social Care, 2016)
The need for competent interprofessional health care professionals is well recognised. Various educational activities have been developed to facilitate the development of interprofessional competence. In this paper we describe an interprofessional, fieldwork experience conducted in a developing country, and the learning gained by the first cohort of students who completed the five week immersion. Eight final year students from Medicine, Occupational Therapy, Physiotherapy and Speech Pathology were interviewed pre- and post-placement by an independent researcher. The transcribed interviews were analysed thematically. Findings indicated that over the placement students gained an appreciation of the skills of the other disciplines and were able to move beyond a textbook definition of what a certain profession did to acquire a real understanding of interprofessional practice. However, students reported that this understanding was predicated on their first clarifying the extent to which they were working in a transdisciplinary or interdisciplinary team, and becoming more confident in their own disciplinary contribution without reliance on formal documentation or standardised assessments. Using daily team discussions, self-reflections and discussions with clinical educators, the students learned to prioritise their busy caseload, share resources and skills, and facilitate team members to achieve therapeutic goals. The interprofessional learning took place in an intercultural context where the students learned to work with children with severe disabilities, with staff with different classroom approaches, and with interpreters, while adjusting emotionally to the level of unmet need of many of the children. Based on the students’ experiences, immersion in an intercultural fieldwork experience is a useful way to facilitate interprofessional learning.